Less severe cerebral palsy outcomes in infants treated with therapeutic hypothermia. (15th October 2015) - Jary, Sally; Smit, Elisa; Liu, Xun; Cowan, Frances M.; Thoresen, Marianne
Abstract: Aim: To describe the incidence, type and severity of cerebral palsy at 24 months in a regional cohort of infants treated with whole‐body therapeutic hypothermia for neonatal encephalopathy. Methods: Data were collected prospectively in a regional centre providing TH. Antenatal and perinatal clinical variables and severity of encephalopathy were collected. Infants were assessed at 18 months using the Bayley Scales of Infant and Toddler Development‐III, and the presence and severity of CP was investigated at 24 months. Results: A total of 125 of 132 infants fulfilled entry criteria for TH trials and completed 72 h of TH. Sixteen (13%) of the 125 infants died, and eight (6%) were not available for follow‐up. Eighteen infants (14%; 18% of those assessed) developed CP. Of these, 12 (67%) were classified using the Gross Motor Function Classification System, at level 1, six (33%) at level 5 and none at levels 2, 3 or 4. Conclusion: Our regional clinical cohort had lower mortality and comparable rates of CP compared with historical outcomes in TH trials. In contrast to historical cohorts, only one‐third of the 18 children with CP were severely affected and 12 were mildly affected, all of whom were independently ambulant by 24 months.